PWE-139 Tace In The Management Of Hcc In A Regional Centre: 5 Year Analysis And Assessment Of Predictors Of Outcome. (9th June 2014) - Morrison, ID; Kasthuri, R; Forrest, EH; Barclay, S; Gillespie, R; Mills, PR; Priest, M; Evans, J; Stanley, AJ
Abstract : Introduction: Transarterial chemoembolisation (TACE) is a useful treatment for selected patients unsuitable for surgical management of hepatocellular carcinoma (HCC). The Hepatoma Arterial-embolization Prognostic (HAP) score has been proposed to be a a better predictor of post-TACE outcome than the Child-Pugh or BCLC (Barcelona clinic liver cancer) scores. 1 Methods: Patients diagnosed with HCC from January 2008 until December 2012 were identified from a prospectively compiled regional MDT database. Patients were risk stratified by Child Pugh grade, BCLC and HAP scores. Response to treatment was assessed by the mRECIST criteria (modified response evaluation criteria in solid tumours). 2 Relationship between risk scores and outcomes were assessed using Log-Rank tests and median survivals. Results: 282 patients were diagnosed with HCC during the study period. 101 of these patients (81 male, 20 female) mean age 66.0 (SD 10.1 years, range 37 to 85) were treated locally with TACE. Aetiology was alcoholic liver disease in 30%, unknown in 21%, non alcoholic liver disease 15%, viral hepatitis 12%, haemochromatosis 8%, other and mixed aetiology 14%. Baseline Child-Pugh grades A, B and C were 76, 21 and 3% respectively. BCLC Staging was A, B, C and D in 25, 58, 13 and 4% respectively. HAP Scores A, B, C and D were 14, 39, 37 and 11% respectively. A total of 228 TACE procedures were performed (mean 2.3 per patient; range 1–6). In 10 (10 %) of patients, TACE was used in combination with radiofrequency ablation and in two (2%) cases it was successfully used as a bridge to transplant. 88% of patients had TACE as sole therapy. Radiological follow-up post TACE was performed in 208 occasions with 18% having a mRECIST complete response, 43% a partial response, 26% static disease and 14% progressive disease. Analysis of the HCC risk stratification scores demonstrates the HAP Score predicted post-TACE survival (p = 0.002), but the Child Pugh (p = 0.192) and BCLC scores (p = 0.210) did not. There was a 3 fold increase in median survival in patients in the HAP A group when compared to those in the HAP D group (36.6 vs. 12.3 months). Conclusion: We report patient survival following TACE for treatment of HCC which compares favourably with published studies. 1 The HAP score for TACE appears promising in our population and superior to existing scores. Reference: Kadalayil et al . A simple prognostic scoring systems for patients receiving transarterial embolisation for hepatocellular cancer. Annals of Oncology 2013;24:2565–2570 Disclosure of Interest: None Declared.